An interference‐aware energy‐efficient routing algorithm with quality of service requirements for software‐defined WSNs. Issue 18 (1st November 2019) - Ding, Zhaoming; Xing, Song; Yan, Feng; Xia, Weiwei; Shen, Lianfeng
Abstract : To address the energy‐efficient (EE) routing problem in software‐defined wireless sensor networks (SDWSNs), in this study, a centralised routing algorithm, namely, the interference‐aware EE routing algorithm (IA‐EERA), is proposed to extend the network lifetime (NL) in SDWSNs. Both the link quality of service requirements and the balance between the link energy loads are considered in the proposed IA‐EERA when selecting the EE relays. Concretely, the IA‐EERA comprises the EE relay selection (RS) and the centralised relay scheduling schemes, which are responsible for generating a valid link set with RS priorities and scheduling the eligible relay nodes with expected link rates from the valid link set, respectively. For supporting the network compatibility and scalability, we propose a hierarchical SDWSN based network architecture, upon which the IA‐EERA can be devoted to solving the EE routing problem in the relay layer of SDWSN. Simulation results show that for one data source without interference, the proposed IA‐EERA can significantly improve the NL compared with the traditional routing algorithm utilising the energy efficiency maximisation. For multiple data sources incurring interference at nodes, the IA‐EERA is able to reduce the NL‐dropping rate by adjusting the interference‐aware parameter that affects the RS priorities